The inconsistency of assessing agricultural zakat - Muhamad Firdaus Abdul Rahman; Azman Abdul Rahman; Luqman Haji Abdullah; Siti Martiah Anwar; Mohd Faez Abu Bakar; Ummu Salamah Ahmad; Hussein 'Azeemi Abdullah Thaidi (Kolej University Islam Sultan Azlan Shah, 2024)
Indexed by Scopus/WOS